Blow-up of solution for quasilinear viscoelastic wave equation with boundary nonlinear damping and source terms - Mi Jin Lee; Jum-Ran Kang; Sun-Hye Park (Boundary Value Problems, 2019)
Abstract In this paper, we consider the blow-up result of solution for a quasilinear viscoelastic wave equation with strong damping and boundary nonlinear damping. We prove a finite time blow-up result of solution with positive initial energy as well as nonpositive initial energy under suitable conditions on the initial data and positive function g.